Making the Eurozone function again: A solution for the European debt problem is hard but not impossible - Vesa Kanniainen (EconPol Forum, 2023)
The Eurozone is stuck in an inefficient equilibrium with high public debt and no policy discipline. The no-bailout rule is not credible. This article proposes a radical two-stage solution for the restructuring of excessive public debt and to eliminate the incentives for undue public borrowing in the future, "Restructuring" would amount to a Euro-wide collective retirement of excess debts. Calculations are presented for two alternative procedures, Borrowing discipline would be restored by the introduction of a tax on subsequent borrowing if it violates a critical level, say a 100 percent debt-to-GDP ratio. This is called a "Tobin tax". The solution suggested, which could be compared with the US state-level rules of a balanced budget requirement, introduces radical policy discipline instead of relying on market discipline, which tends to come too late.
Keywords: 330